2010
DOI: 10.1111/j.1471-0307.2010.00614.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of heat treatment of ovine milk on the compositional and sensory properties of set yoghurt

Abstract: The aim of this study was to investigate the effect of heat treatment of ovine milk at 60°C ⁄ 5 min and 90°C ⁄ 5 min (control group) on the compositional and sensory properties of set yoghurt (n = 40). The concentration of apparent casein and total whey protein were significantly higher while sensory properties (except consistency) were not significantly different from the yoghurts in control group (P < 0.05). The results showed that ovine set yoghurt produced by heat treatment at low temperature possessed hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 16 publications
(20 reference statements)
1
11
0
Order By: Relevance
“…The presence of Cr was found only in Farm 1. Its extremely low value (0.01 mg/kg milk) agrees with the results of Zamberlin et al (2012), who reported a mean value between 0.01 mg/kg and 0.04 mg/kg. Bilandžić et al (2015) found a content equal to 34 µg/ kg.…”
Section: Resultssupporting
confidence: 90%
“…The presence of Cr was found only in Farm 1. Its extremely low value (0.01 mg/kg milk) agrees with the results of Zamberlin et al (2012), who reported a mean value between 0.01 mg/kg and 0.04 mg/kg. Bilandžić et al (2015) found a content equal to 34 µg/ kg.…”
Section: Resultssupporting
confidence: 90%
“…R. sphaerocarpa shrub is rich in its mineral composition , it contains considerable amounts of Ca (8.62g.kg -1 ), Mg (3.11g.kg -1 ), Na (2.21g. kg -1 ) and (P 2.24g.kg -1 ); while zinc and Mn in leaves were 0.04g.kg -1 and 0.03g.kg -1 , respectively (Zamberlin et al, 2012;Abdenour et al, 2020). Based on their chemical composition, the leaves of R. sphaerocarpa showed high fiber (NDF= 598 g.kg-1 DM and ADF= 432g.kg -1 DM), lignin contents (ADL =178g.kg -1 DM) and the crude protein (CP=137g.kg -1 ) (Abdenour et al, 2020).…”
Section: Phytochemistry Of Retama Speciesmentioning
confidence: 96%
“…Studies have shown that micronutrients in the human body make up only 4% of total body weight but are part of every tissue, body fluid, cell, and organ [2]. They act as catalysts in many biological reactions in the body, such as muscle contraction and nerve impulse transmission, and help to utilize nutrients from food [3,4]. The mineral composition of milk can be affected by the heat treatment of milk, so mineral concentrations in raw milk are higher compared to heattreated milk [5,6].…”
Section: Introductionmentioning
confidence: 99%